Determination of optimal pressure parameters for the system of pulp microaeration dispersants in column flotation - D. R. Magomedov; A. K. Koizhanova; G. Toktar; N. A. Abdyldayev; A. N. Bakrayeva (Metalurgija, 2023)
The article presents the results of experiments intended to beneficiate gold-bearing mineral raw materials by column flotation with the use of micro aeration of pulp through a dispersant system. The influence of the pressure level in the pressure system of dispersants within the range from 202,65 to 1013,25 KPa was studied during the experiments. It was found that the parameter of 607,95 KPa enables to achieve the optimal balance of the precious metal mass yield and the content in the concentrate, with a final gold recovery of 87 %.